Clinical Outcome of Degenerative Mitral Regurgitation: Critical Importance of Echocardiographic Quantitative Assessment in Routine Practice. Issue 13 (25th September 2018) - Antoine, Clemence; Benfari, Giovanni; Michelena, Hector I.; Maalouf, Joseph F.; Nkomo, Vuyisile T.; Thapa, Prabin; Enriquez-Sarano, Maurice
Abstract : Background: Echocardiographic quantitation of degenerative mitral regurgitation (DMR) is recommended whenever possible in clinical guidelines but is criticized and its scalability to routine clinical practice doubted. We hypothesized that echocardiographic DMR quantitation, performed in routine clinical practice by multiple practitioners, predicts independently long-term survival and thus is essential to DMR management. Methods: We included patients diagnosed with isolated mitral valve prolapse from 2003 to 2011 and any degree of mitral regurgitation quantified by any physician/sonographer in routine clinical practice. Clinical/echocardiographic data acquired at diagnosis were retrieved electronically. The end point was mortality under medical treatment analyzed by Kaplan-Meier method and proportional hazard models. Results: The cohort included 3914 patients (55% male) mean age (±standard deviation) 62±17 years with left ventricular ejection fraction 63±8% and median after routinely-measured effective regurgitant orifice area (EROA) [interquartile range], 19 [0–40] mm 2 . During follow-up (6.7±3.1 years), 696 patients died under medical management, and 1263 underwent mitral surgery. In multivariate analysis, routinely-measured EROA was associated with mortality (adjusted hazard ratio, 1.19; 95% confidence interval, 1.13–1.24; P <0.0001 per 10 mm 2 ) independently of left ventricular ejection fraction and end-systolic diameter, symptoms, and age/comorbidities. The association between routinely-measured EROA and mortality persisted with competitive risk modeling (adjusted hazard ratio, 1.15; 95% confidence interval, 1.10–1.20; P <0.0001 per 10 mm 2 ), or in patients without guideline-based class I/II surgical triggers (adjusted hazard ratio, 1.19; 95% confidence interval, 1.10–1.28; P <0.0001 per 10 mm 2 ) and in all subgroups examined (all P <0.01). Spline curve analysis showed that, compared with general population mortality, excess mortality appears for moderate DMR (EROA ≥20 mm 2 ), becomes notable at EROA ≥30 mm 2, and steadily increases with higher EROA levels (eg, higher EROA levels beyond the 40 mm 2 threshold). Conclusions: Echocardiographic DMR quantitation is scalable to routine practice and is independently associated with clinical outcome. Routinely-measured EROA is strongly associated with long-term survival under medical treatment. Excess mortality versus the general population appears in the moderate DMR range and steadily increases with higher EROA. Hence, individual EROA values should be integrated into therapeutic considerations, in addition to categorical DMR grading. Abstract : Supplemental Digital Content is available in the text.